If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (-4) = x + (-12) 2x + -4 = x + (-12) Reorder the terms: -4 + 2x = x + (-12) -4 + 2x = x + -12 Reorder the terms: -4 + 2x = -12 + x Solving -4 + 2x = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 2x + -1x = -12 + x + -1x Combine like terms: 2x + -1x = 1x -4 + 1x = -12 + x + -1x Combine like terms: x + -1x = 0 -4 + 1x = -12 + 0 -4 + 1x = -12 Add '4' to each side of the equation. -4 + 4 + 1x = -12 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = -12 + 4 1x = -12 + 4 Combine like terms: -12 + 4 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 2+x+2x+4=x+16 | | 20n-28=1on+2 | | 8v-25=v+80 | | 10x-6=3x+4 | | n+(n+32)=119 | | 3n+.5n=42 | | n^2+14n=-48 | | 6x(3)y(3)+7xy-8x(2)y=0 | | 25x+5=30x^2+6x | | 4t-5=t+7 | | 3n^2+30=23n | | (3x+5)(x^2-x-12)=0 | | .666666667(y-12)=-6 | | 20x^2-dx-d^2=0 | | 5a^2+14a=-8 | | 3x-8y=16 | | x^2+2x-86=-23 | | x/7=13/10 | | 14x^2-5x=6 | | 90-5s=13 | | 3.6+(-1.7)= | | 15p^2-28=-23p | | -10+x+4-5=7x-10 | | -5(3+-5)= | | 7-5x=67 | | -10+x+4=7x-10 | | b+11=2b | | 3a+7=4a | | 3n^2=-24-17n | | 25-.8= | | -10x+90=-x | | 3(1+2y)=y+2y+4y |